Econometric Analysis of the Causality between Energy Supply and GDP: The Case of Malaysia - Lau, Evan; Tan, Chiang Ching (Elsevier, 2014)
This study investigates the causal interplay between four major domains of energy supply i.e., oil, petroleum, gas and coal and economic growth (GDP) in Malaysia. For this purpose, cointegration, Granger causality and variance decomposition tests have been applied. The major findings extract from this paper are as follows: (1) Long run relationships are detected between GDP and energy supply (in oil and coal types). (2) Short run unidirectional causality exists running from GDP to energy supply (petroleum and gas) while long run causality was detected from oil and coal towards GDP. (3) The results of the variance decompositions suggest that the impact of GDP to energy supply become noticeable only over the longer period of time, implying that energy saving measures can smooth the path of economic growth in the long run. In order to sustain long term growth, it is necessary to increase investment in supply of energy and technology progress while at the same time increase the efficiency in energy usage for the country. This could strike the balance of environmental concern, economic growth, sustainability and energy security for Malaysia.